Gestational weight gain and group prenatal care: a systematic review and meta-analysis - Michelle A. Kominiarek; Adam K. Lewkowitz; Ebony Carter; Susan A. Fowler; Melissa Simon (BMC, 2019)
Abstract Background Group visits for chronic medical conditions in non-pregnant populations have demonstrated successful outcomes including greater weight loss compared to individual visits for weight management. It is plausible that group prenatal care can similarly assist women in meeting gestational weight gain goals. The purpose of this study was to evaluate the effect of group vs. traditional prenatal care on gestational weight gain. Methods A keyword search of Medline, Embase, Scopus, Cochrane Database of Systematic Reviews, Database of Abstracts of Reviews of Effects, Cochrane Central Register of Controlled Trials, clinicaltrials.gov, and Google Scholar was performed up to April 2017. Studies were included if they compared gestational weight gain in a group prenatal care setting to traditional prenatal care in either randomized controlled trials, cohort, or case-control studies. The primary and secondary outcomes were excessive and adequate gestational weight gain according to the Institute of Medicine guidelines. Heterogeneity was assessed with the Q test and I2 statistic. Pooled relative risks (RRs) and confidence intervals (CI) were reported with random-effects models from the randomized controlled trials (RCT) and cohort studies. Results One RCT, one secondary analysis of an RCT, one study with "random assignment", and twelve cohort studies met the inclusion criteria for a total of 13,779 subjects. Thirteen studies used the CenteringPregnancy model, defined by 10 sessions that emphasize goal setting and self-monitoring. Studies targeted specific populations such as adolescents, African-Americans, Hispanics, active-duty military or their spouses, and women with obesity or gestational diabetes. There were no significant differences in excessive [7 studies: pooled rates 47% (1806/3582) vs. 43% (3839/8521), RR 1.09, 95% CI 0.97-1.23] or adequate gestational weight gain [6 studies: pooled rates 31% (798/2875) vs. 30% (1410/5187), RR 0.92, 95% CI 0.79-1.08] in group and traditional prenatal care among the nine studies that reported categorical gestational weight gain outcomes in the meta-analysis. Conclusions Group prenatal care was not associated with excessive or adequate gestational weight gain in the meta-analysis. Since outcomes were overall inconsistent, we propose that prenatal care models (e.g., group vs. traditional) should be evaluated in a more rigorous fashion with respect to gestational weight gain.